In The Midst Of Payment System Digitalization, Why Are There Still MSMEs That Have Not Used QRIS? - Ayu Annisa Rahmawati; Agung Dharmawan Buchdadi; M. Edo Suryawan Siregar (Journal of Indonesian Management, 2023)
This research intends to analyze the reasons that influence MSMEs to be reluctant or not willing to use QRIS. This study uses a qualitative method, with primary data sources collected through online questionnaires. The population in this research were MSMEs in Brebes Regency, Central Java. The samples collected were 53 respondents. The results of this research indicate that the reason with the highest percentage of MSMEs has not used QRIS is that they do not know information about QRIS, the number of consumers who use mobile payments is not large, and they are more comfortable using cash.